Meningkatkan Hasil Belajar Shooting Dalam Sepakbola Melalui Pendekatan Permainan Bola Inovatif (Department of Physical Education, Sport, Health and Recreation, 2015)
This research was conducted at the District 02 Elementary School Bojong Bojong Tegal with class IV studysubjects by the number of 30 students consisting of 18 boys and 12 student daughter. This study uses 2 cycles,where each cycle consists of 1) planning, 2) implementation of action 3) observation; 4) reflection. This research is a learning object shooting by using innovative ball game. Data collection techniques were used thatdocumentation, observation sheet (observation), written and practical test, completeness assessment of learning outcomes through the use of data analysis techniques percentage description. This research method is Classroom Action Research.The results showed that the application of innovative methods of ball games canimprove learning outcomes shooting football in the fourth-grade students of SD Negeri 02 Bojong District ofTegal Bojong Year 2014 From the results of the analysis are improving student learning outcomes from the firstcycle to the second cycle